Determinasi Risiko Terhadap Kinerja Bank Syariah Digital: Bank Aladin Syariah Tbk Tahun 2018-2023 - Muhammad, Mahatir (Business Finance Analyst Co., 2025)
This study aims to analyze the influence of liquidity risk (Financing to Deposit Ratio / FDR), operational risk (Operating Costs to Operating Income / BOPO), and market risk (Net Interest Margin / NIM) on financial performance as measured through Return on Assets (ROA) at Bank Aladin Syariah Tbk during the period 2018–2023. As a sharia-based digital bank entity, Bank Aladin faces a complexity of risks that demand a responsive and integrated management strategy. The analysis method used was multiple linear regression with secondary data. The results showed that simultaneously, the three independent variables did not have a significant effect on ROA. Partially, FDR, BOPO, and NIM also showed no significant influence. However, a determination coefficient value (R²) of 0.730 indicates that 73% of ROA variations can be explained by these three variables. These findings affirm the importance of increasing the effectiveness of liquidity and market risk management in improving the financial performance of digital Islamic banks. This research makes a strategic contribution to the development of more adaptive risk management policies. The limitation in the number of samples is an important note and recommended for further research with a wider range of data to obtain more representative results